Synthesis, characterization and biocompatibility studies of zinc oxide (ZnO) nanorods for biomedical application - Gopikrishnan, R.; Zhang, K.; Ravichandran, P.; Baluchamy, S.; Ramesh, V.; Biradar, S.; Ramesh, P.; Pradhan, J.; Hall, J. C.; Pradhan, A. K.; Ramesh, G. T. (Nano-Micro Letters, 2010)
Nanoparticles are increasingly being recognized for their potential utility in biological applications including nanomedicine. Here, we have synthesized zinc oxide (ZnO) nanorods using zinc acetate and hexamethylenetetramine as precursors followed by characterizing using X-ray diffraction, fourier transform infrared spectroscopy, scanning electron microscopy and transmission electron microscopy. The growth of synthesized zinc oxide nanorods was found to be very close to its hexagonal nature, which is confirmed by X-ray diffraction. The nanorod was grown perpendicular to the long-axis and grew along the [001] direction, which is the nature of ZnO growth. The morphology of synthesized ZnO nanorods from the individual crystalline nucleus was confirmed by scanning and transmission electron microscopy. The length of the nanorod was estimated to be around 21 nm in diameter and 50 nm in length. Our toxicology studies showed that synthesized ZnO nanorods exposure on hela cells has no significant induction of oxidative stress or cell death even in higher concentration (10 μg/ml). The results suggest that ZnO nanorods might be a safer nanomaterial for biological applications.